Analysis of Wood Carbohydrates: A New Scheme - Evstigneyev, Edward I. (Fine Chemical Engineering, 2025)
A new scheme for the analysis of wood carbohydrates is proposed, which includes measurements of cellulose and non-cellulose polysaccharides. The analysis is based on the color reaction of monosaccharides in hydrolysates of polysaccharides with phenol in the presence of concentrated sulfuric acid. The method is highly sensitive: the concentration of monosaccharides in the mixture prepared for analysis is determined at the level of 1 × 10-4 M. For the analysis, 0.25 cm3 of the hydrolysate, previously diluted 10 times, is sufficient. The total time for the analysis of the hydrolysate, including sample preparation, does not exceed 30 minutes. The method allows for a relatively simple and highly accurate determination of polysaccharides both in plant raw materials (agricultural plants, softwood, and hardwood) and in lignin samples (softly isolated and technical).